Gastrointestinal Endoscopy Performed by Gastroenterologists: Opportunistic Screening Strategy for Newly Diagnosed Head and Neck Cancers - Yang, Chih-Wei; Chu, Yueng-Hsiang; Chen, Hsin-Chien; Huang, Wei-Chen; Chen, Peng-Jen; Chang, Wei-Kuo (Frontiers in Oncology, 2022)
Aim Approximately 66% of head and neck cancers are diagnosed at an advanced stage. This prospective study aimed to detect newly diagnosed head and neck cancers using regular upper gastrointestinal (UGI) endoscopy with oral-pharynx-larynx examination. Methods A total of 2,849 patients underwent UGI endoscopy with an additional oral-pharynx-larynx examination. Patients aged < 20 years, those who were pregnant, had a history of head and neck cancers, were undergoing emergency endoscopy, and had a poor laryngopharyngeal view were excluded. The symptoms, incidence, location, pathology, and stage of malignant neoplasms were investigated. Results A total of 2,720 patients were enrolled. Endoscopically observable 23 abnormal findings (0.85%) included 18 (0.66%) benign lesions and 5 (0.18%) newly diagnosed malignant neoplasms. Notably, 4 (80%) of 5 patients with malignant neoplasms were diagnosed at an early stage (Stage 0, I, and II). Conclusions UGI endoscopy with oral-pharynx-larynx examination can achieve opportunistic head neck cancer screening and is recommended for every patient in endoscopy units.